Simulating the line balance to provide an improvement plan for optimal production and costing in petrochemical industries - Asghar Hemmati; Farshad Kaveh; Milad Abolghasemian; Adel Pourghader chobar (مدیریت مهندسی و رایانش نرم)
This research examines the influential factors and theoretical principles of queuing in balancing production lines. The required information, including the number of active machines on the production line, the level of station idleness, and the waiting time for parts to receive services, has been quantitatively gathered through on-site observations and interviews with managers and supervisors. Process modeling has been developed using the ARENA simulation software version 13, which can identify the current status of tank and heavy product production in terms of queuing and line balance criteria, and its results are analyzed and described. The findings of this research indicate that the addition of a forklift increases costs from 65,902 monetary units to 80,577, equivalent to a 22% increase. However, this change results in a doubling of production compared to the current state; therefore, the extra expenditure due to increased production is satisfactory for the managers of this organization. The significance of this production increase aligns with enhanced productivity, especially considering the greater emphasis placed on production targets.